Time-dependent, cumulative and threshold effects of air pollution – RSV interaction: a narrative review - Wrotek, August Edwin; Badyda, Artur; Jackowska, Teresa (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Respiratory syncytial virus (RSV) is a leading cause of respiratory infections in children. An association between air pollution and RSV has received worldwide attention because pollution may contribute to both increased morbidity and disease severity. However, data on this topic are limited, especially in children, and the results may be equivocal because each air pollutant may have a direct effect, the effect may be delayed (lag effect), dependent on threshold level(s) or accumulation of a pollutant, and the pollutants often interact. The objective of this paper was to review the literature in this area, identify knowledge gaps, and present a detailed analysis of the air pollution-RSV interaction with emphasis on time and concentration dependence.